The Early Development of Islamic Law: Examining the Rational and Flexible Nature of Compilation and Standardization - Fachrurozi; Mohammad Subhi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The establishment of standard law serves as a crucial framework for Muslims, particularly in mitigating confusion following the death of the Prophet Muhammad. This study examines the compilation and standardization of Islamic law during the formative years of Islam, emphasizing the contributions of the Companions, who brought diverse backgrounds and perspectives to the discourse. The analysis begins with the historical context of how Islamic law was compiled and standardized, progressing to an exploration of the characteristics of Islamic law as articulated by jurists (mujtahid). Through a comprehensive literature review, this paper aims to demonstrate the historical evolution of Islamic law, highlighting its rational, open, and flexible nature. These attributes reflect the positive implications of Islamic teachings, which are both transparent and characterized by the principle of rahmatan li al-'alamin (mercy to the worlds). Furthermore, this study elucidates the connection between the inclusive and humanistic spirit of Islam and the Islamic legal framework developed by early scholars, underscoring its rationality, flexibility, dynamism, and accessibility.